Marketing digital de la peluquería Jesús. - Villavicencio Torres, Hally Caroline (2022)
Digital marketing has gained strength in recent times, the advancement of technology has allowed the use of this tool in different market niches, it is defined as the grouping of strategies aimed at promoting a brand on the internet, facilitating the marketing of a good or service. It differs from traditional marketing by including the use of channels and methods that allow the analysis of results in real time. However, there are still businesses that are unaware of marketing, such as the case of Peluquería Jesús located on Rocafuerte and 9 de Octubre streets in Baba Canton; that through this investigation the ignorance of digital marketing was detected as one of the reasons that make up the company's problems, not carrying out adequate advertising or having an obsolete one, not using social networks as a strategy to carry out discounts and promotions in the service offered in this hairdressing salon, since the application of strategies is estimated as one of the most crucial components for the profitability of a business, it is also important to highlight that these elements are essential to be known and have a position in the market.